Students’ Perception and Challenges on the Use of Self-Assessment in English Writing Competence at Junior High School - -, Ni Putu Lia Agustini; Ni Luh Putu Eka Sulistia Dewi; Anak Agung Gede Yudha Paramartha; Luh Gede Eka Wahyuni (Universitas Pendidikan Ganesha, 2024)
Teachers experience concerns regarding the lack of consistency in implementation and the absence of clear guidelines in lesson planning, including problems in developing teaching materials for teachers. Therefore, teachers think that implementing self-assessment has various challenges. One of them is the challenge that comes from students. This study aims to analyze students' perceptions of using self-assessment to improve writing competence at Junior High School. The study involved students from grades 7 and 8 to identify their views towards the use of self-assessment and the challenges they face. The research method used a survey with a qualitative approach. Data were collected through surveys and interviews and analyzed using the thematic analysis method. The results showed that students tend to have a positive perception of the application of self-assessment, students become more confident in designing writing, and motivated students to improve the quality of their writing with self-awareness so that it will meet students' expectations in writing so that it makes it easier for students to determine sustainable learning strategies and can improve students' writing skills. However, there are some challenges identified such as students still feeling confused in assessing their writing, lack of understanding of the assessment criteria, and students' fear of criticism and negative self-evaluation.